Geometry of circles and texture cues for coral shape and absolute size measurement - Tusara, Loren M.; Soriano,Maricor N. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2010)
In this thesis, a calibration procedure is proposed using the geometry of circles in order to provide absolute estimates of size for surfaces derived using shape-from-texture. To our knowledge, there is no existing calibration method for shape-from-texture object reconstruction. This search aims to quantify coral growth using a one-shot measurement approach - only a single 2D image is needed to perform the surface shape reconstruction of a coral colony. Computing for absolute size measurement of the reconstruction allows us to measure the volume of an object. Thereafter other measurements can be derived such as coral rugosity, coral growth and mortality rate, and surface area, among others. The proposed calibration technique is derived from the geometry of circles to arrive to a value for the depth calibration.
Thesis (Master of Science in Physics)--University of the Philippines Diliman
Keywords: Corals -- Imaging; Corals -- Colonies